Does It Matter If the Content Is Generated by Generative AI? A Rapid Literature Review of Academic Integrity, Ethics, and Pedagogical Implications - Joshua Ebere Chukwuere (Journal of Information System and Informatics, 2026)
The current wave of adoption and use of generative artificial intelligence (GenAI) across various human sectors, particularly in higher education, has prompted debate and discussion about its applications and ethical implications in higher education. This paper presents insight into the question and ongoing debate: Does it matter if the content is generated or written by GenAI? To contribute to ongoing debates and discussions, this article employed a rapid literature review research methodology to examine literature articles within the timeframe of 2024 to March 2025, involving 59 scientific papers across databases such as Scopus, ResearchGate, and Web of Science, as well as grey literature on Google Scholar. The methodology enabled the researcher to review past technological evolution, draw inferences, and link it to the current wave of AI and GenAI in higher education. The paper found that the evolution of computers and technology has raised many questions, tech stress issues, and discussions, which remain worrisome even to this day. The study found that the ongoing debate and discussions on the impact and ethical implications of GenAI in higher education still confuse both academics and non-academics about the future of GenAI. However, the document provided answers to the ongoing question and highlighted some recommendations for the effective application of GenAI in higher education institutions (HEIs).